The environmental impacts consequences of the qualitative characteristics and the surface area change of water of Habbaniyah Lake - Mutar, Zeyad Frayeh (Al-Adab Journal, 2021)
Lakes are among the important water resources projects, the presence of which has some advantages and disadvantages that are reflected in the environment and surrounding areas. Despite the many positives of Lake Habbaniyah, at the same time it causes a comprehensive reversal of environmental conditions. As is well known, nature has eternal rules and regulations, and it does not give more than what it used to do without charge. The surface area of ​​Habbaniyah Lake changes according to the incoming water expenses, which ranged between (128 - 389) km2 for the period (2000-2019) and this rise and decrease in water levels has environmental impacts on agricultural lands and residential use with high levels of groundwater in the residential areas adjacent to the lake , While the low water levels led to water pollution, especially colon bacteria of (1337) cells / ml, and the high percentage of salts by approximately (1080) mg / liter.